Occupation-related respiratory diseases among sanitary workers in the workplace: a systematic review and meta-analysis - Tolera, Sina Temesgen; Alemu, Bezatu; Mengistu, Dechasa Adare; Deressa, Alemayehu (Frontiers in Public Health, 2024)
IntroductionEmerging evidence from both developed and developing countries indicates that occupation-related respiratory diseases (ORRD) among sanitary workers constitute a significant public health challenge. These are because of the working environment, where employees are more likely to be at risk in an unsafe workplace, especially sanitary workers. Therefore, the purpose of this systematic review and meta-analysis was to estimate the prevalence of ORRD among sanitary workers.MethodsThe Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram was used, and the Population, Intervention, Comparison, Outcomes, and Study (PICOS) framework was applied to structure the review questions. Studies published in English from 2000 to 2022 were searched in databases and through other methods. Boolean logic (AND, OR, NOT), Medical Subject Headings (MeSH), and keywords were used as follows: (Occupational “OR” Job “OR” Work) AND (Respiratory tract diseases “OR” Respiratory tract infections “OR” Respiratory tract symptoms “OR” Respiratory tract problems) AND (Solid waste collectors “OR” Sewage workers “OR” Street sweepers “OR” Waste treatment worker) AND Countries. Stata MP/17 software was used for data analysis. A random effects model and restricted maximum likelihood were applied. A generic precomputed effect size for the prevalence of ORRD was employed at a 95% confidence interval (CI:95%).ResultsA total of 23 studies were included, four from industrialized countries (n = 4) and seven from developing countries (n = 7), out of an initial 123 studies. Among the 4,521 sanitary workers, 1990 (44%), 1,651 (37%), and 880 (19%) were SS, SWCs, and STWs, respectively. Globally, the pooled prevalence of ORRD among all SWs was 32.56% (95%CI: 25.78, 39.34%). Among these, high-income and low-income countries had a prevalence of 20% (95%CI: 18.08%, 0.21.96%) and 35.17% (95%CI: 27.48, 42.76%), respectively. In the SS and SWC groups, the prevalence was 36.41% (95%CI: 26.69%) and 31.28% (95%CI, 18.64, 43.92%), respectively.ConclusionThe current systematic review and meta-analysis found that ORRD were common among the SWs. Due to numerous risk factors, these illnesses are more prevalent in low-income countries than in industrialized ones. Therefore, to reduce these risks for these groups—especially for street sweepers in low-income countries—government policy changes and other preventive measures are required.